Effect of storage of oestrual mucus on in vitro penetrability of buffalo spermatozoa - KAUSHAL, G; PANGAONKAR, G R; SHARMA, R K; MATHAROO, J S (The Indian Journal of Animal Sciences, 2014)
Bovine oestrual mucus was stored at 2 different temperatures for different periods of time to study the effect of temperature and duration of storage on physical properties of oestrual mucus and sperm penetrability. Physical properties of oestrual mucus did change following prolonged storage. The quality and degree of arborisation get deteriorated as the period of storage increased. Consistency also cqanged to watery with prolonged storage. However, pH and colour of oestrual mucus remained unatlected. Mucus samples could be stored for 8 days without any significant effect on sperm penetration. However, storage of mucus for 60Â·days seriously affected the sperm penetration. Temperature of storage did not have any significant effect on physical properties or sperm penetrability.